BACKGROUND TO LANGUAGE LEARNING AND FACTORS WHICH CAN INFLUENCE MOTIVATION - Kipchakova, Sanobar; Hasanov, Khumoyun (Educational Research in Universal Sciences, 2023)
This article discusses the factors which can influence motivation while learning foreign languages, the ways of developing different strategies of a lesson and provides some tips for improving language learning. Also, it describes possible solutions for dealing with the anticipated problems.